Developmental delay in 3-month-old low birth weight infants with hyperbilirubinemia - Wiradharma Wiradharma; I Gusti Ayu Trisna Windiani; Ekawaty Lutfia Haksari (Indonesian Pediatric Society Publishing House, 2013)
Backgrourui Developmental delay may be due to a variety of factors occurring during the prenatal, perinatal, or postnatal periods, one of which is hyperbilirubinemia. Objective To evaluate the impact ofhyperbilirubinemia on infant developmental delay. Methods A prospective cohort study was conducted from March to July 2011. Subjects were low birth weight infants with and without hyperbilirubinemia. Developmental delay was measured using the Mullen Scales of Early Learning. Data was analyzed by Chi square test and relative risks were calculated. Logistic regression analysis was performed to assess factors associated with developmental delay. Differences were considered statistically significant for P values < 0.05. Results Forty-six low birth weight infants were enrolled in this study, 23 with hyperbilirubinemia and 23 without hyperbilirubinemia. The relative risk (RR) for developmental delay in the hyperbilirubinemia group was 2.08 (95%CI 0.51 to 8 .40). Multivariate analysis revealed that hyperbilirubinemia did not significantly influence developmental delay (RR 1.45; 95%CI 0.29 to 7.31). However, small for gestational age with or without hyperbilirubinemia significantly influenced developmental delay (RR 12.13; 95%CI 2.43 to 60.56). Conclusion Hyperbilirubinemia in low birth weight infants is n ot a risk factor for developmental delay at the age of 3 months. However, being small for gestational age with or without hyperbilirubinemia significantly influences the likelihood of developmental delay.